Mechanical and electronic properties of ternary alloys XY3Ti11 - Kasparyan, S. O.; Ordabaev, A. E.; Bakulin, A. V.; Kulkova, S. E. (Russian physics journal, 2025)
The electronic structure and elastic properties of four series of titanium alloys of composition XY 3 Ti 11 , where X and Y are elements of IIIA, IVA, IVB–VIB groups, is studied by the projector augmented-wave method using the cluster-plus-glue-atom model. The smallest values of the Young’s modulus in each series are 37.30 GPa for InHf 3 Ti 11 , 36.52 GPa for SnHf 3 Ti 11 , 65.72 GPa for CrIn 3 Ti 11 , and 52.39 GPa for WSn 3 Ti 11 . The peculiarities of the electronic structure of alloys due to their chemical composition are discussed. It is shown that s, p‑elements do not affect the character of the Young’s modulus anisotropy in the alloy series: the lowest value corresponds to the < 100> direction, and the highest one—the < 111> direction, while d‑elements can change it.